2003
DOI: 10.1046/j.1471-4159.2003.01758.x
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of α‐amino‐3‐hydroxy‐5‐methylisoxazole‐4‐propionate receptor transmission in the suprachiasmatic nucleus by aniracetam enhances photic responses of the biological clock in rodents

Abstract: This study was designed to test whether the a-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA) receptorfacilitating drug, aniracetam, could potentiate photic responses of the biological clock in the suprachiasmatic nucleus (SCN) of rodents. Using the whole-cell patch technique, we first demonstrated that AMPA currents elicited by either local AMPA application or optic chiasm stimulation were augmented by aniracetam in the neurons of the SCN. The AMPA application-elicited increase of intracellular Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Actually, Mintz and coworkers reported that the degree of NMDA-induced phase-advances during the late subjective night was lower than that of light pulse-induced, although the phase-delays during the early subjective night obtained by both methods were quite similar [11]. Interestingly, Moriya and coworkers reported that aniracetam, an enhancer of AMPAR activity, augmented light-induced phase-shifts at CT14, but not at CT20 [21]. These findings strongly suggest that light-induced phase-advances during the late subjective night need not only glutamatergic stimuli, but also additional factor(s).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, Mintz and coworkers reported that the degree of NMDA-induced phase-advances during the late subjective night was lower than that of light pulse-induced, although the phase-delays during the early subjective night obtained by both methods were quite similar [11]. Interestingly, Moriya and coworkers reported that aniracetam, an enhancer of AMPAR activity, augmented light-induced phase-shifts at CT14, but not at CT20 [21]. These findings strongly suggest that light-induced phase-advances during the late subjective night need not only glutamatergic stimuli, but also additional factor(s).…”
Section: Discussionmentioning
confidence: 99%
“…In the SCN slices in vitro , Shibata and coworkers demonstrated that AMPA application induced phase-shifts of neuronal firing rhythms similar to NMDA [13]. Moreover, it was recently shown that AMPA application increased the calcium concentration in the SCN slices [21]. These studies prompted us to re-evaluate the effects of AMPA both on the regulation of phase-shifts of behavioral rhythms and on clock gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Our evidence suggests that PACAP regulation of the magnitude of AMPA currents is dependent upon PAC1 receptors and the adenylyl cyclase-signalling cascade. Interestingly, a recent study found evidence suggesting that the enhancement of AMPA mediated synaptic transmission in the SCN is sufficient to increase the magnitude of light-induced phase delays [ 52 ]. Finally, PACAP can increase Ca 2+ by itself as well as enhance AMPA- and glutamate -evoked increases in Ca 2+ [ 16 , 17 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 in (Brown, 2016)]. Application of pharmacological mimics of the light-input pathways to living SCN slices, such as glutamate or the glutamate receptor agonists AMPA and NMDA, also causes phase shifts in the electrical rhythms that imitate the lightinduced shifts in locomotor activity (Colwell & Menaker, 1992;Shibata et al, 1994;Biello et al, 1997;Ding et al, 1998;Moriya et al, 2000Moriya et al, , 2003. Similarly, optogenetic manipulation of SCN activity causes phase shifts in electrical and gene expression rhythms both in vivo and in vitro (Jones et al, 2015).…”
Section: Function Of Neuronal Oscillations In the Scnmentioning
confidence: 99%